Bioremediation of Oil-Contaminated Soil with Variations of Bacterial Cultures and Nutrient Ratio-Field-Scale Experimental Research - Limbong, Barita Amjani; Tangahu, Bieby Voijant (Universitas Syiah Kuala, 2025)
The spread of hydrocarbon contamination in the form of oil-contaminated soil originates from waste from drilling and oil production. Hydrocarbon contaminants are categorized as hazardous and toxic waste (B3) that has long been deposited in the soil, disrupting the soil ecosystem and the groundwater cycle. Remediation of oil-contaminated soil is carried out using ex-situ bioremediation technology. Oil-contaminated soil is excavated using heavy equipment, collected at the contaminated site, and then transported to a licensed B3 waste treatment facility. The study aims to evaluate the degradation of Total Petroleum Hydrocarbon (TPH) over time using biostimulation and bioaugmentation methods to meet the success parameters of the quality standards for the Total Concentration (TK) of long-chain Petroleum Hydrocarbon (PH) (with a PH value TK-B 0.5% (5000 mg/kg). Biostimulation uses urea fertilizer as a source of N and SP-36 fertilizer as a source of phosphorus with treatment variations of C:N:P ratios of 100:10:1 and 100:5:1. Bioaugmentation uses variations in the treatment of indigenous bacteria that are naturally available in contaminated soil and variations with the addition of non-indigenous bacteria from bacterial cultures. The results of the study showed that the fastest bioremediation time to achieve the success parameters of the quality standards was 28 days with an average degradation rate of 3%/day. The 2-factor Analysis of Variance (ANOVA) statistical test with 4 replications produced a P-value = 0.257 ( 0.05) so that the C:N:P ratio did not have a significant effect on the decrease in concentration. TPH. The C:N:P ratio of 100:5:1 showed a higher percentage of TPH degradation compared to the C:N:P ratio of 100:10:1. There was no significant difference in the rate of TPH degradation between the treatment variations of indigenous bacteria and mixing with non-indigenous bacteria. The approach to calculating the population spike of non-indigenous bacteria mixing using logarithmic units showed a population spike of 0.06 log10 (1.14 times) 0.5 log10 (3.16 times). The non-indigenous bacterial inoculum survived but did not dominate the degradation pathway due to bacterial competition and a single dose that was too low. Environmental parameters such as pH, humidity and temperature were in ideal conditions during the study.